Negativity and information in campaign advertising - Sullivan, Jonathan (2010)
In many democracies election campaign advertising is an important form of communication between parties and candidates and voters. There is however an uncomfortable tension between what campaigns should achieve (according to democratic theories) and what they are like in reality. In Taiwan, political scientists have voiced concerns about the excessively negative tone of party and candidate advertising. Descriptive single-election accounts also suggest that campaign ads in Taiwan regularly fail to provide voters with the substantive information they need to make reasoned choices. These observations are cited as reason to conceive campaign advertising as deleterious to Taiwan’s new democracy. However, recent work in the US, suggests that negative advertising may in fact be a source of useful information to voters. By extension, the authors of these studies claim that negative ads make an important contribution to democratic political competition. The central objective of the thesis is to explore these claims in the Taiwan context. Are the theoretical arguments used to explain the content of negative advertising in the US supported by empirical evidence in the highly dissimilar Taiwanese context? Do negative ads in Taiwan, in spite of prior scholarly observations to the contrary, make a useful contribution to the information environment available to voters? In addressing these questions, the thesis aims to contribute a non-western case study to general research on campaign advertising. It also aims to provide the Taiwan studies field with a more systematic account of campaign communications than is currently available. To this end, the study analyzes more than 500 TV and newspaper ads from all four Presidential elections held to date.